Mechanisms of tendon-bone interface healing: biomechanics, cell mechanics, and tissue engineering approaches - Zhixiong Xu; Wensheng Xu; Tao Zhang; Long Luo (Journal of Orthopaedic Surgery and Research)
Abstract The healing of tendon-bone contact surfaces involves complex biomechanical and biochemical interactions, with pivotal implications for sports medicine and rehabilitation. This review explores applications from cellular mechanics to tissue engineering, emphasizing how biomechanics impact tendon-bone healing. Cells regulate behavior, including growth, differentiation, and migration, by sensing mechanical signals and translating them into biochemical responses, which are critical in the healing process. Cellular mechanics modulate intracellular signaling, thereby influencing biological function and healing capacity. Optimizing tendon-bone interface repair involves modulating the extracellular mechanical environment. This includes physical stimulation, such as stretching, pressure, or vibration, to promote cellular alignment and enhance tissue structural integrity. Tissue engineering in tendon-bone healing focuses on designing scaffolds that mimic the biomechanical properties of the natural tendon-bone interface. Synthesizing these studies provides an in-depth understanding and utilization of biomechanical principles, significantly improving tendon-bone healing and offering new directions for clinical treatments to achieve better therapeutic outcomes and rehabilitation for patients with sports injuries.